Aprendizagem empreendedora: estudo com microempresários de empresas incubadas - Nascimento, Raimunda Letícia do (2018)
The entrepreneurial learning is a continuous and experiential process where the entrepreneurs when based on their experiences learn to recognize opportunities and act on them, starting and managing an enterprise. There is still a lack in literature about the theme which causes the need of a theoretical and empirical development (WANG;CHUNH, 2014).Knowing how the process of transformation (exploration and exploitation) and how the entrepreneurs learn in clusters, communities and network is a gap to be supplied for the improvement in that research field. Considering the business incubators as propitious environment to qualify the entrepreneur and amplify his relationship network, the present study has as general aim to investigate how the entrepreneurial learning occurs in micro entrepreneurs from business incubators. To that extent, it was analyzed how those entrepreneurs have transformed their career experiences into knowledge, checking the process of transformation and the influencing factors. As theoretical base it was used the entrepreneurial learning model by Politis (2005). Methodologically, the research was qualitative and descriptive. It was done semi-structured interviews with 14 entrepreneurs from business incubators inside the net of business incubators in Ceará. The data were processed by content analysis and operationalized in the ATLAS.ti 7 software. The results reveal that the entrepreneurs have experiences in companies creation, in management and in a specific business sector. In reference to the transformation process, it was verified that some of the interviewee used the exploration and others used exploitation and some of them used both, but the first one have a higher incidence. The factors that motivate that process are the failure in previews events, the causation logic as a dominant rationality and a specialist career guidance. Lastly, it was found that the entrepreneurs from a business incubator acquired entrepreneurial learning throughout their careers that increased their effectiveness in recognizing opportunities and also how to learn with the responsibilities resulting from the new business.